Contrast-To-Noise Ratio Differences between Iodine and Calcium on Virtual Monochromatic Images (VMI) In Dual Energy Computed Tomography (DECT) - Sarah I. Izmi,; Choirul Anam,; Heri Sutanto,; Ariij Naufal,; Riska Amilia,; Pingky S. Dewi,; Hilda S. Putri,; Revita Dewantari,; Indah R. Ilham,; Ilham Alkian,; Adiwasono M. B. Setiawan, (International Journal of Scientific Research in Science and Technology, 2024)
Contrast-to-noise ratio (CNR) is an important parameter in evaluating the quality of virtual monochromatic images (VMI), especially for distinguishing materials with different atomic numbers. This study aims to evaluate the CNR difference between iodine and calcium on VMI images in dual energy computed tomography (DECT) using an in-house phantom. The in-house phantom had ten holes filled with iodine (with concentrations of 5, 7.5, 10, and 15 mg/ml) and calcium (with concentrations of 200, 300, 500, and 600 mg/ml). The in-house phantom was scanned using a GE Revolution DECT type Ultrafast kV Switching. The input parameters were tube voltage of 80/140 kV, tube current of 370 mA, rotation time of 0.5 s, slice thickness of 5 mm, field of view of 25 cm. Projection data were reconstructed to obtain VMI images (with energies of 50, 60, 70, 80, 90, and 100 keV). The results showed that increasing concentrations of iodine and calcium lead to in CNR. At low energies (50-70 keV), the CNR of calcium is higher than that of iodine, while at high energies (80-100 keV), the difference in CNR is more pronounced. In conclusion, calcium showed a more significant increase in CNR compared to iodine, particularly at low energies and high concentrations, with the difference becoming more pronounced at high energies.
Keywords: virtual monochromatic images (VMI); dual energy computed tomography (DECT); contrast-to-noise ratio (CNR)